UNCOVERING THE PROCESS OF GENDER-RESPONSIVE BUDGETING OF THE PUBLIC SECTOR IN GORONTALO - Rahmatia, Rahmatia; Nur, Fuad; Syata, Wahyu Muh. (Economos : Jurnal Ekonomi dan Bisnis, 2023)
This research aims to effectively analyze the gender-responsive budgeting process in the public sector that takes gender interests into account in the Gorontalo Provincial Office of Women's Empowerment and Child Protection. This research uses qualitative methods with a qualitative descriptive approach. The data sources are primary data and secondary data. Data collection techniques include observation, interviews, documentation, and literature research. Data analysis techniques use the following steps: data collection, data reduction, data display, verification, and conclusion. The results showed that there were three gender-responsive activities carried out in Gorontalo, namely increasing women's economic productivity, increasing institutional capacity for gender mainstreaming, and institutional strengthening. The management of gender-responsive budgeting starts with gender-responsive budget planning, budgeting gender-responsive activities, implementing gender-responsive budgeting, and monitoring and evaluating gender-responsive budgeting. Through gender-responsive budgeting, it is expected to make a major contribution to the achievement of women's empowerment goals and realize gender welfare and justice in various fields of development in Gorontalo Province.